(untitled) (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2020)
This paper describes the implementation of a cryptographic attack by the boomerang method on the "AL01" block symmetric algorithm, one of the encryption algorithms which are developed at the Institute of information and computational technologies of the SC MES RK. Taking into account the basic properties of the differential cryptanalysis and based on the conclusions of other scientific works, the necessary minimum number of a set of quartets of open and corresponding closed texts is determined. The article concludes that the proposed cryptographic algorithm is highly resistant to this type of cryptographic attack.